Profile of Teenage Pregnancy in Hadramout, Yemen - Salim Bin Ghouth, Abdulla; Saleh Bin Break, Ahlam; Ali Melkat, Adnan; Salmeen Belafair, Amer (Journal of Women's Reproductive Health, 2017)
Objective: A cross-sectional study was designed to collect socio-demographic and obstetric data about female teenagers who have pregnancy and visiting primary health care centers for antenatal care. Subjects and methods: Data were collected by a trained 60 medical students of the 6th level in Hadramout University during their post in primary health care centers from 20 May – 10 June 2008. A convenience sample of 237 teenagers who were attending the 12 PHC centers for antenatal care checking constituted the study subjects. Results: Fifty-one out of 237 (21.5%) pregnant women were of age 17 years or less. Most of them were from rural areas with statistically significant difference in both age groups (p-value <0.002),they were housewives (232/237 97.8%) and their husband’s mostly had non-professional jobs with a significant difference between both age groups (p-value <0.005). A high prevalence of anemia in teenage pregnant women was reported (76.7% of them had Hb level less than 11 g/dl) but there were no significant difference between mean Hb level in those at age of 17 years or less (9.9 SD=1) and those at age >17-<20 years (10.1 SD=1.18) p-value >0.05 About one-third of pregnant teenagers were second or multigravida (81/237 pregnant women 34.2%) but only 66 of them were delivered before. The majority of second/multigravida were delivered normally (57/66 pregnant women 86.4%) while only 31 of them (47%) gets their births in a health facility where LSCS was done for 9 pregnant women. The outcome of the pregnancy in teenage multigravida are 67 children; three of them were stillbirth and other 6 babies died within the first week of their life indicating the total children died during the perinatal period as 9 children ; so the perinatal mortality rate was very high in teenagers (9/67*1000 = 134/1000 births). Conclusions: Teenage pregnancy is common and accepted in Hadramout in Yemen; the main consequences are a high prevalence of anemia and high perinatal mortality rate.
Keywords: Teenage Pregnancy; Yemen; Antenatal Care; Anemia; Primary Health Care